Analyses of Ukrainian companies listed on the Warsaw Stock Exchange - Cymański Maciej (My University, 2008)
Polish capital market as well as the Warsaw Stock Exchange is young, but not immature. The WSE dynamically grows and successfully competes with other stock exchanges in Europe. It is well regulated, reliable and innovative. The number of foreign companies listed in this institution increases. Ukrainian capital market needs reforms which can help with its deficiencies, so large Ukrainian companies choose stocks exchanges in other countries. Astarta Holding N.V. is a large vertically-integrated Ukrainian company that debuted in the WSE in 2006. It produces white sugar from sugar-beets and successfully increases share of its own raw-materials used for the production. Kernel Group of Companies debuted in the WSE in 2007. They produce bottled sun-flower oil, but also sell and fright crops. This paper consists of description of Polish and Ukrainian capital markets. The description and comparison of the Polish Warsaw Stock Exchange (WSE) and the Ukrainian First Security Trading System (PFTS) was also provided. It gives a clue why Ukrainian companies in question have chosen WSE for debuts and shows advantages and disadvantages of both exchanges. There are two purposes of this research. The first one is to check whether the WSE is an attractive place of gaining capital for Ukrainian companies. The answer is - yes. It gives several advantages for them e.g. low costs of gaining capital, investors from Western Europe, localization – place of debut is a place of operations for some firms. The second purpose is to check if debuts of two companies listed on the WSE were a success – they are vertically-integrated companies and have wide access to raw-materials. The history, activity and debuts of both companies were provided. In addition, financial analyses had to be done to evaluate their attractiveness for investors. First two weeks on the WSE considered as debuts were not a success, it means that investors did not appreciate advantages of Astarta and were cautious about financial analysis’ results of Kernel. The paper describes these issues in details.
Analizy Ukraińskich spółek giełdowych notowanych na Warszawskiej Giełdzie Papierów Wartościowych
Keywords: analysis; Ukrainian companies; Warsaw Stock Exchange; comparative analysis; financial analysis; capital market; PFTS Stock Exchange